PERAN KELUARGA DALAM MENGHINDARI TOXIC FAMILY BAGI PERKEMBANGAN REMAJA - Az Zahra, Salsabila; Silvianis Diwanti, Yusrinda (Jurnal Ilmiah Penelitian Psikologi, 2022)
The purpose of OFQS (Online Friendship Quality Scale) creation is to measure online friendship quality between 18-24 years old college students. It could also facilitate users to evaluate friendship quality dynamics, then enhance their friendship quality. The six domains of friendship are Validation and Caring, Conflict and Betrayal, Conflict and Resolution, Companionship and Recreation, Help and Guidance, and Intimate Exchange (Asher & Parker, 1993). OFQS is a self-report questionnaire that scales from (1) not at all like me to (5) very much like me. OFQS was developed during 2021 using convenience sampling. Respondents during the development process are FPUAJ college students that do online interaction with their best friends, and currently 18-24 years old (number of respondents = 219, average (M) age of respondents = 19.51, dan SD of respondents age = 1.23). Item analysis is done through Spearman corrected item total correlation and Mann-Whitney U-test that eliminates 3 out of 54 items. Companionship and Recreation domain is the only domain that is not valid. Reliability test found that the Cronbach alpha’s value is reliable with a score of 0,851. People who complete this test will get a description of their friendship quality for every domain that comes in three categories (Good, Enough, and Not Good). Scoring categories are based on norm-referenced standardization procedures. Further research is needed for other demographics such as workers.